Let $f(x)=\lim\limits_{n \rightarrow \infty}\left\{\frac{n^n(x+n)\left(x+\frac{n}{2}\right) ...\left(x+\frac{n}{n}\right)}{n !\left(x^2+n^2\right)\left(x^2+\frac{n^2}{4}\right) ...\left(x^2+\frac{n^2}{n^2}\right)}\right\}^{x / n}$, for all x > 0. Then, (a) $f\left(\frac{1}{2}\right) \geq f(1)$ |
(a), (b) (b), (c) (c), (d) (a), (d) |
(b), (c) |
We have, $f(x)=\lim\limits_{n \rightarrow \infty}\left\{\frac{n^n(x+n)\left(x+\frac{n}{2}\right) ...\left(x+\frac{n}{n}\right)}{n !\left(x^2+n^2\right)\left(x^2+\frac{n^2}{4}\right) ...\left(x^2+\frac{n^2}{n^2}\right)}\right\}^{x / n}$ $\Rightarrow \log f(x)=\lim\limits_{n \rightarrow \infty} \frac{x}{n} \log \left\{\prod_{r=1}^n \frac{\left(x+\frac{n}{r}\right)}{\left(x^2+\frac{n^2}{r^2}\right)} . \frac{n}{r}\right\}$ $\Rightarrow \log f(x)=\lim\limits_{n \rightarrow \infty} \frac{x}{n} \sum\limits_{r=1}^n \log \left\{\frac{1+\frac{r}{n} x}{1+\left(\frac{r}{n} x\right)^2}\right\}$ $\Rightarrow \log f(x)=x \lim\limits_{n \rightarrow \infty} \sum\limits_{r=1}^n \log \left\{\frac{1+\frac{r}{n} x}{1+\left(\frac{r}{n} x\right)^2}\right\} \frac{1}{n}$ $\Rightarrow \log f(x)=x \int\limits_0^1 \log \left\{\frac{1+t x}{1+(t x)^2}\right\} d t$ $\Rightarrow \log f(x)=\int\limits_0^x \log \left(\frac{1+u}{1+u^2}\right) d u$, where $u=t x$ $\Rightarrow \frac{f'(x)}{f(x)}=\log \left(\frac{1+x}{1+x^2}\right)$ .....(i) We observe that $f(x)>0$ for all $x>0$. Also, $\log \left(\frac{1+x}{1+x^2}\right)>0 \Leftrightarrow \frac{1+x}{1+x^2}>1 \Leftrightarrow x>x^2 \Leftrightarrow 0<x<1$ ∴ $\frac{f'(x)}{f(x)}>0$ for $0<x<1$ and $\frac{f'(x)}{f(x)}<0$ for $x>1$ $\Rightarrow f'(x)>0$ for $0<x<1$ and $f'(x)<0$ for $x>1$ ...(ii) $\Rightarrow f(x)$ is increasing on $(0,1)$ and decreasing on $(1, \infty)$. $\Rightarrow f\left(\frac{1}{2}\right) \leq f(1)$ and $f\left(\frac{1}{3}\right) \leq f\left(\frac{2}{3}\right)$ So, option (b) is correct and option (a) is incorrect. From (ii), we obtain $f'(2)<0$. So, option (c) is correct. From (i), we obtain $\frac{f'(3)}{f(3)}-\frac{f'(2)}{f(2)}=\log \frac{4}{10}-\log \frac{3}{5}=\log \left(\frac{2}{3}\right)<0$ $\Rightarrow \frac{f'(3)}{f(3)}<\frac{f'(2)}{f(2)}$. So, option (d) is not correct. |